2020
DOI: 10.1002/jcla.23299
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA NEAT1/microRNA‐125a axis predicts increased major adverse cardiac and cerebrovascular event risk independently in patients with unprotected left main coronary artery disease underwent coronary artery bypass grafting

Abstract: Background The study aimed to investigate the long noncoding RNA nuclear‐enriched abundant transcript 1 (lnc‐NEAT1) and microRNA‐125a (miR‐125a) expressions, and further explore the role of lnc‐NEAT1/miR‐125a axis in predicting major adverse cardiac and cerebrovascular event (MACCE) risk in patients with unprotected left main coronary artery disease (ULMCAD) underwent coronary artery bypass grafting (CABG). Methods A total of 280 patients with ULMCAD underwent CABG were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“… 12 LncRNA nuclear‐enriched abundant transcript 1 (NEAT1), a structural component of paraspeckles, is known to modulate the expression of multiple genes through nuclear retention. 13 More importantly, NEAT1 is implicated in the stability in tumorigenesis and development of PCa. 14 Expanding on the role of NEAT1, a previous study unveiled that NEAT1 participates in the process of osteogenic differentiation potentials of human bone marrow‐derived mesenchymal stem cells (hBMSCs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 LncRNA nuclear‐enriched abundant transcript 1 (NEAT1), a structural component of paraspeckles, is known to modulate the expression of multiple genes through nuclear retention. 13 More importantly, NEAT1 is implicated in the stability in tumorigenesis and development of PCa. 14 Expanding on the role of NEAT1, a previous study unveiled that NEAT1 participates in the process of osteogenic differentiation potentials of human bone marrow‐derived mesenchymal stem cells (hBMSCs).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, exosomes derived from tumor cells could transfer a reporter gene into the germ line in vivo , implying exosomes as an information carrier from somatic cells to gametes 12 . LncRNA nuclear‐enriched abundant transcript 1 (NEAT1), a structural component of paraspeckles, is known to modulate the expression of multiple genes through nuclear retention 13 . More importantly, NEAT1 is implicated in the stability in tumorigenesis and development of PCa 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a type of noncoding RNA that comprise of longer than 200 nucleotides sequences, and hold strong promise as biomarkers and therapeutic targets for cancer due to their genome-wide expression in various tissues and the tissue specific expression characteristics [ 7 ]. LncRNA nuclear paraspeckle assembly transcript 1 (NEAT1) has been established as a structural component of paraspeckles, which modulates multiple genes’ expression through nuclear retention [ 8 ]. In a previously conducted study, NEAT1 was confirmed to accelerate the metastasis of ovarian cancer cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 Furthermore, some studies exhibit that lnc-NEAT1 binding with microRNA-125a (miR-125a) participates in the pathogenesis of multiple human diseases (including multiple myeloma, acute ischemic stroke, and coronary artery disease). [15][16][17] In terms of AR, although one study explores that lnc-NEAT1 together with miR-125a manifests close correlation with the disease risk of AR, it only surveys AR patients whose ages are above 18 years and collects their inferior turbinate mucosa, while as mentioned above, AR occurs in the pediatric population to a large extent, and it is inconvenient to collect their nasal mucosa under local anesthesia. 18 Hence, this study enrolled 80 pediatric AR patients, 40 nonallergic nasal pediatric patients, and 40 healthy pediatric subjects to detect their lnc-NEAT1 and miR-125a expressions in the peripheral blood, aiming to investigate the correlation of circulating lnc-NEAT1 and miR-125a with disease risk and severity of pediatric AR, also to explore their associations with T helper (Th)1, Th2 cells and their secreted cytokines in the pediatric AR patients.…”
Section: Introductionmentioning
confidence: 99%